2000
DOI: 10.1098/rspb.2000.0978
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal and extinction in fragmented landscapes

Abstract: Evolutionary and population dynamics models suggest that the migration rate will affect the probability of survival in fragmented landscapes. Using data for butterfly species in the fragmented British landscape and in immediately adjoining areas of the European continent, this paper shows that species of intermediate mobility have declined most, followed by those of low mobility, whereas high-mobility species are generally surviving well. Compared to the more sedentary species, species of intermediate mobility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
265
2
15

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(292 citation statements)
references
References 48 publications
10
265
2
15
Order By: Relevance
“…On the other hand, low mobility decreases the cost of losing emigrating individuals from small stands. Therefore the extinction rate in a fragmented landscape might be lower for species like O. eremita than for species with higher dispersal rate (Hill et al 1996;Thomas 2000). The occupancy pattern of O. eremita is consistent with this, as it indicates that the beetle is able to remain over quite long periods in small stands without connectivity, even though long term persistence might be impossible (Ranius 2000).…”
Section: Dispersal Patternssupporting
confidence: 65%
See 1 more Smart Citation
“…On the other hand, low mobility decreases the cost of losing emigrating individuals from small stands. Therefore the extinction rate in a fragmented landscape might be lower for species like O. eremita than for species with higher dispersal rate (Hill et al 1996;Thomas 2000). The occupancy pattern of O. eremita is consistent with this, as it indicates that the beetle is able to remain over quite long periods in small stands without connectivity, even though long term persistence might be impossible (Ranius 2000).…”
Section: Dispersal Patternssupporting
confidence: 65%
“…The dispersal rate of O. eremita seems to be in the same range as for sedentary butterflies, whose populations conform to a metapopulation structure (Thomas and Hanski 1997;Thomas 2000). In O. eremita also, it might be possible for local populations in individual trees to become extinct, without immediate recolonization, although the tree is suitable and there are neighbouring trees with the beetle present.…”
Section: Dispersal Patternsmentioning
confidence: 94%
“…The discussion in Maciel and Lutscher (2013) gives several ecological examples that make it clear that there is no single solution for all cases. For example, Thomas (2000) found that high-mobility butterflies had the highest probability of surviving in fragmented landscapes. Assuming all other things are equal, we could conclude from Figure 4.4 that Case M would model individual movement in this scenario.…”
Section: Chapter 7 Discussionmentioning
confidence: 99%
“…According to the theoretical predictions, less genetically diverse populations are often characterised by lower viability (Frankham 2003;Reed and Frankham 2003;Aguilar et al 2008) and/or adaptability (Young et al 1996, Willi et al 2006. However, the risk of negative consequences of fragmentation is related primarily to the dispersal capability (Thomas 2000). Dispersal is a means for both colonisation of new habitats and gene exchange among populations (Howe and Smallwood 1982;Travis and Dytham 1998).…”
Section: Introductionmentioning
confidence: 99%